A CRISPR-associated factor Csa3a regulates DNA damage repair in Crenarchaeon Sulfolobus islandicus. Issue 17 (24th August 2020) - Liu, Zhenzhen; Sun, Mengmeng; Liu, Jilin; Liu, Tao; Ye, Qing; Li, Yingjun; Peng, Nan
Abstract: CRISPR−Cas system provides acquired immunity against invasive genetic elements in prokaryotes. In both bacteria and archaea, transcriptional factors play important roles in regulation of CRISPR adaptation and interference. In the model Crenarchaeon Sulfolobus islandicus, a CRISPR-associated factor Csa3a triggers CRISPR adaptation and activates CRISPR RNA transcription for the immunity. However, regulation of DNA repair systems for repairing the genomic DNA damages caused by the CRISPR self-immunity is less understood. Here, according to the transcriptome and reporter gene data, we found that deletion of the csa3a gene down-regulated the DNA damage response (DDR) genes, including the ups and ced genes. Furthermore, in vitro analyses demonstrated that Csa3a specifically bound the DDR gene promoters. Microscopic analysis showed that deletion of csa3a significantly inhibited DNA damage-induced cell aggregation. Moreover, the flow cytometry study and survival rate analysis revealed that the csa3a deletion strain was more sensitive to the DNA-damaging reagent. Importantly, CRISPR self-targeting and DNA transfer experiments revealed that Csa3a was involved in regulating Ups- and Ced-mediated repair of CRISPR-damaged host genomic DNA. These results explain the interplay between Csa3a functions in activating CRISPR adaptation and DNA repair systems, and expands our understanding of the lost link between CRISPR self-immunity and genome stability.